Just-in-time postnatal education programmes to improve newborn care practices: needs and opportunities in low-resource settings. Issue 7 (29th July 2020) - Subramanian, Laura; Murthy, Seema; Bogam, Prasad; Yan, Shirley D; Marx Delaney, Megan; Goodwin, Christian D G; Bobanski, Lauren; Rangarajan, Arjun S; Bhowmik, Anindita; Kashyap, Sehj; Ramnarayan, Nikhil; Hawrusik, Rebecca; et al.
Abstract : Worldwide, many newborns die in the first month of life, with most deaths happening in low/middle-income countries (LMICs). Families' use of evidence-based newborn care practices in the home and timely care-seeking for illness can save newborn lives. Postnatal education is an important investment to improve families' use of evidence-based newborn care practices, yet there are gaps in the literature on postnatal education programmes that have been evaluated to date. Recent findings from a 13 000+ person survey in 3 states in India show opportunities for improvement in postnatal education for mothers and families and their use of newborn care practices in the home. Our survey data and the literature suggest the need to incorporate the following strategies into future postnatal education programming: implement structured predischarge education with postdischarge reinforcement, using a multipronged teaching approach to reach whole families with education on multiple newborn care practices. Researchers need to conduct robust evaluation on postnatal education models incorporating these programee elements in the LMIC context, as well as explore whether this type of education model can work for other health areas that are critical for families to survive and thrive.